A Project Report on Configurable and Pluggable Json Producer and Consumer for An Affiliation Program - ANCHAL VERMA, DEEP DUTTA (2014)
INTERNAL GUIDE: Mrs. SANCHARI SAHA, MVJCE CD ONLY
Keywords: Pluggable Json Producer and Consumer for An Affiliation Program